STRATEGI DALAM MENINGKATKAN KINERJA KARYAWAN MELALUI PELATIHAN DAN KOMITMEN ORGANISASI - Karmilawati Karmilawati; K Kurniawansyah; Sri Rahayu (Jurnal Ekonomi & Bisnis, 2023)
This study aims to examine strategies for improving employee performance, namely through training and organizational commitment. The type of data used in this study was quantitative data obtained directly through questionnaires distributed to research respondents who were scored (scoring). The subjects used as respondents in this study were all 20 employees of the Tambora Hotel at Sumbawa Besar. The data that has been collected is processed using the SPSS program to be studied using techniques that include multiple linear regression analysis, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determinant coefficient test (R2). The results of this study showed that the training and organizational commitment have a positive and significant effect on employee performance, both partially and simultaneously. The ability of training variables and organizational commitment to influence changes in employee performance variables is 80.5%, while the remaining 19.5% is influenced by other variables outside this research model, such as compensation or incentives, work motivation, and work environment.